Examining public private partnerships in ASEAN countries : The role of investment climate - Emirullah, Chandra; Hussain, Mohammad Azam (General Association of the Economists in Romania (AGER), 2014)
Evidently, the ASEAN countries are among those which have achieved remarkable economic growth rates in the world.But they are facing significant infrastructure bottlenecks which can threaten the sustainability of their development, if not solved effectively and efficiently well in time. Apparently, Public Private Partnership (PPP) arrangement promises to be an ideal solution for developing countries that have limited fiscal capacity such as ASEAN. However, PPP performance in this region is not very encouraging compared with other countries.This study attempts to look at the role of investment climate especially the economic and political factors that may affect the economic growth performance of PPP projects.For empirical investigation panel data approach is utilized, where mostly the estimated coefficients exhibit expected signs but are not statistically significant.Besides, each country has unobserved special characteristics that can affect the conduciveness of PPPs which should also be considered by policymakers.